If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3m + 4n + -2m + 5m + -2n + -7p = 0 Reorder the terms: -3m + -2m + 5m + 4n + -2n + -7p = 0 Combine like terms: -3m + -2m = -5m -5m + 5m + 4n + -2n + -7p = 0 Combine like terms: -5m + 5m = 0 0 + 4n + -2n + -7p = 0 4n + -2n + -7p = 0 Combine like terms: 4n + -2n = 2n 2n + -7p = 0 Solving 2n + -7p = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7p' to each side of the equation. 2n + -7p + 7p = 0 + 7p Combine like terms: -7p + 7p = 0 2n + 0 = 0 + 7p 2n = 0 + 7p Remove the zero: 2n = 7p Divide each side by '2'. n = 3.5p Simplifying n = 3.5p
| x^2-16=11 | | 4m-8m-(2m+3)=2(3m-7.5) | | 2z-3=6 | | 4n-12=-24 | | 5x+31=2x+13 | | (1/2)(2x-4)+(1/3)(x+2)=2 | | x+16=4x+1 | | 3x-14x-5=0 | | y=-4.9t^2+20t+65 | | 4(x-1)+1=3(2x+1) | | -6x-12=-30 | | x^2+25=23 | | (x^2+4)=16 | | -3(x-4)=-3x-12 | | -4=64x | | -1x+7x=21 | | H=-5t^2+30t+135 | | 9360+624t-4.9t^2=0 | | -4(5x+2)=12 | | -7+1=-20 | | -6x-12=30 | | 5-2n=13 | | 9x^2=-9x+4 | | 10(t-9)-9(5-6t)=2(4t-1)+5+10t | | -5x+10=15 | | 12.8x-19.3= | | 6-x=8+x | | -11x+15=-4x-20 | | -7+2x-19-9x=-61 | | 114-3x=15x+20 | | 5x+4=-3x+12 | | 11x+7=29 |